The portfolio theory of inflation and policy (in)effectiveness revisited: Corroborating evidence - Biagio Bossone; Andrea Cuccia (Kiel Institute for the World Economy (IfW), 2020)
This study revisits and tests empirically the Portfolio Theory of Inflation (PTI), which analyzes how the effectiveness of macroeconomic policy in open and globally financially integrated economies is influenced by global investor decisions (Bossone, The portfolio theory of inflation and policy (in)effectiveness, 2019). The PTI shows that when an economy is heavily indebted and is perceived by the market to be poorly credible, investors hold it to a tighter intertemporal budget constraint and policies aimed to stimulate output growth dissipate into domestic currency depreciation and higher inflation, with limited or no impact on output, or with lower output and lower inflation. On the other hand, markets afford highly credible economies much greater space for effective and noninflationary macro policies. The study leads to a very basic advice: policymakers of an internationally highly integrated economy should keep public liabilities (the stock of both central bank money and public debt) at low levels: the larger the liabilities, the higher the degree of surrender of the country's national policy sovereignty to external forces and interests.
Keywords: E31; E4; E5; E62; F31; G15; H3; 330; credibility; exchange rate; financial integration; fiscal and monetary policies; global investor(s); inflation; intertemporal budget constraint; policy effectiveness; public debt